Understanding the Utilization of Wasted Bread as a Brewing Adjunct for Producing a Sustainable Wheat Craft Beer - Katry Dall’Acua; Manuela Poletto Klein; Bárbara Iegli Tech; Alessandra Fontana; Ludmylla Tamara Crepalde; Roger Wagner; Fernanda de Candido de Oliveira; Voltaire Sant’Anna (Microorganisms)
Wasted bread (WB) has been studied as an alternative ingredient for increasing the sustainable footprint in the beer production chain. There are gaps in the literature on the impact of WB on beer manufacturing. Thus, the objective was to evaluate the addition of WB as a replacement for wheat flakes in a craft beer. Three formulations with different concentrations of WB were produced and monitored for glucose and maltose concentrations in the mash; the beer was analyzed for ethanol, glycerol, acetic acid, lactic acid, pH, acidity, turbidity, color, and volatile compounds. Sensory analysis was performed by a trained panel. In the initial stages of mashing, a higher concentration of sugars was found in the wort with WB added, while, at the end stages, this was higher in the control wort. The addition of WB resulted in beers with a lower turbidity, darker color, and lower concentrations of ethanol, glycerol, and acetic acid. Among the volatile compounds, D-limonene, ethyl dodecanoate, heptanol, acetaldehyde, and ethyl acetate should be further explored as markers for the presence of WB. Higher intensities of banana odor and flavors were observed by the trained panel when there was a greater substitution of wheat flakes. WB is a low-cost and effective ingredient for beer production, although more work is needed for its large-scale use.